Legal Communication Of The Parties And An Unconcluded Contract. Qualification Problems Of Subjective Transaction Elements - Viktorovna Zaytseva, Natalia (Opción, 2019)
The article deals with the issues of constituent parts of legal relationship, as well as the concept of legal relationship as the basis of civil liability. The doctrine of counter execution, existing in English law - as the main evidence of the conclusion of the contract, the peculiarities of determin- ing the moment of entry into force of the contract in the civil law of the Russian Federation, as well as the emergence of a legal phenomenon in the form of an unconcluded contract. Research objective: to define the concept of legal relationship as a mandatory condition for the entry into force of the contract, and the intersection of this concept with the concept of the contract to assess the possibility, if there is a legal rela- tionship between the parties to the civil law relations of the contract by an unconcluded. Methods: General scientific methods: Interpretations, descriptions and comparisons, and privately applied scientific methods: Comparative legal, analytical and system analysis methods. Results: The conducted research showed that the renunciation of the subjective component of the legal relationship and the absence of mechanisms to correctly qualify the legal relationship of the parties led to the creation of such legal phenomena as an unconcluded contract, in the presence of an explicit expression of will of the parties to conclude it. Conclusions: If the legal system leaves the issues of evaluation of will and expression of will only in the plane of judicial discretion, this in most cases will not con- tribute to the effective legal regulation and creation of sustainable business rules. The exercise by the law of its functions is possible only through the establishment of clear mechanisms to qualify the conduct of the parties, and not only through a literal interpretation of the text of the contract, recorded on paper.